Teacher's Corrective Feedback In Teaching Writing Recount Text To The First Year Of SMA Muhammadiyah I Surakarta In 2011/2012 Academic Year - Yuliyanti, Ratih Nasalia (2012)
This study is aimed at describing: 1) the types of coorrective feedback in teaching learning of writing recount text, and 2) the problems faced by the teacher in teaching writing recount text. In achieving the objectives, the researcher used descriptive qualitative as an approach to collect and analyze the data. The research was held in SMA Muhammadiyah 1 Surakarta. The research took two classess of the first year students as the subject of the study. The writer gets the data of the research from event, informant, and document. The techniques of collecting data are the observation and interview about the writing teaching- learning process. The result of the analysis shows that teacher corrective feedback technique is appropriate and effective for the second year student of SMA Muhammadiyah 1 Surakarta in teaching writing recount text. By using this technique, the students are capable of knowing their errors, the reason and correct it. So, it can facilitate the teaching- learning writing process. The teacher has several problems in teaching namely difficulty in explaining the content of the text, students' difficulties in developing paragraph in recount text, students' difficulties in mastering component of writing, and lacking of media.